Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Hang Nguyen Mai

giải pt: (4x-3)(2x-1)=(x-3)(4x-3) giải

hộ mình

 

Nguyễn Thái Hoàng Anh
20 tháng 2 2020 lúc 18:56

=> (2x-1)=(x-3)(4x-3)/(4x-3)

=> 2x-1=x-3

=> 2x-x=4

=> x=4

Khách vãng lai đã xóa

Bài làm

( 4x - 3 )( 2x - 1 ) = ( x - 3 )( 4x - 3 )

<=> ( 4x - 3 )( 2x - 1 ) - ( x - 3 )( 4x - 3 ) = 0

<=> ( 4x - 3 )( 2x - 1 - x + 3 ) = 0

<=> ( 4x - 3 )( x + 2 ) = 0

<=> 4x - 3 = 0 và x + 2 = 0

<=> x = 3/4 và x= -2

Vậy S={3/4; -2 }

Khách vãng lai đã xóa

Các câu hỏi tương tự
anh minh
Xem chi tiết
hoang xuan dieu
Xem chi tiết
nguyễn khánh linh
Xem chi tiết
Nguyễn Thùy Linh
Xem chi tiết
pham hoang
Xem chi tiết
Nguyễn Yến Nhi
Xem chi tiết
phạm hoài thương
Xem chi tiết
nguyên công quyên
Xem chi tiết
Lê Hồng Ngọc
Xem chi tiết